Integrative taxonomy of a new cocculinid limpet dominating the Aurora Vent Field in the central Arctic ocean. Issue 10 (12th October 2022) - Chen, Chong; Hilário, Ana; Rodrigues, Clara F.; Ramirez-Llodra, Eva
Abstract : Deep-sea hydrothermal vents host lush chemosynthetic communities, dominated by endemic fauna that cannot live in other ecosystems. Despite over 500 active vents found worldwide, the Arctic has remained a little-studied piece of vent biogeography. Though located as early as 2001, the faunal communities of the Aurora Vent Field on the ultra-slow spreading Gakkel Ridge remained unsampled until recently, owing to difficulties with sampling on complex topography below permanent ice. Here, we report an unusual cocculinid limpet abundant on inactive chimneys in Aurora (3883–3884 m depth), describing it as Cocculina aurora n. sp. using an integrative approach combining traditional dissection, electron microscopy, molecular phylogeny, and three-dimensional anatomical reconstruction. Gross anatomy of the new species was typical for Cocculina, but it has a unique radula with broad, multi-cuspid rachidian where the outermost lateral is reduced compared to typical cocculinids. A phylogenetic reconstruction using the mitochondrial COI gene also confirmed its placement in Cocculina . Only the second cocculinid found at vents following the description of the Antarctic Cocculina enigmadonta, this is currently the sole cocculinid restricted to vents. Our discovery adds to the evidence that Arctic vents host animal communities closely associated with wood falls and distinct from other parts of the world.